Hyperglycemia induces inflammatory mediators in the human chorionic villous - Corrêa-Silva, Simone [UNESP] (2018)
This study was based on the hypothesis that IL-1β and its central regulator, the inflammasome, may play a role in the inflammatory condition exhibited by placental tissues from mothers with different gestational hyperglycemia levels. Pregnant women were classified according to the glycemic reference as non-diabetic (n = 15), mild gestational hyperglycemia (n = 15), gestational diabetes mellitus (n = 15) and type 2 diabetes mellitus (n = 15). We investigated levels of pro-inflammatory factors in maternal plasma and placental tissues (by ELISA or immunohistochemistry) and, NFKB activity (by electrophoretic mobility shift assay) and inflammasome protein expression (by Western blot) in chorionic villous. Maternal plasma and placental levels of inflammatory factors (IL-1β IL-6, and MCP-1) were increased during all hyperglycemic conditions. Villous stroma cells showed strong immunoreactivity to CD68. In addition, with syncytiotrophoblast, the villous stroma cells were also stained to detect iNOS, MCP-1, TLR2, and TLR4. Although the levels of protein had fluctuated in the groups, NLRP1, NLRP3, ASC, and Caspase 1 were up-regulated in all hyperglycemic groups suggesting the inflammasome may be assembled in these pregnant women. The NFKB activity also exhibited higher levels in hyperglycemic groups, which might imply in pro-inflammatory cytokines production. In summary, increased maternal glucose levels during pregnancy changed systemic and placental inflammatory patterns, which occurred in parallel with the expression of inflammasome factors and processing and secretion of the pro-inflammatory cytokine IL-1β. These results suggest an inflammatory condition in all gestational hyperglycemic conditions, even in hyperglycemia that is less severe than gestational or overt diabetes, likely associated with inflammasome activation and inflammatory cytokine secretion. Inflammasome activation as a possible source of inflammatory factors may be an important target to be considered while managing hyperglycemia and preventing adverse pregnancy outcomes.